Staphylococcus aureus versus neutrophil: Scrutiny of ancient combat. (June 2019) - Nasser, Ahmad; Moradi, Melika; Jazireian, Parham; Safari, Hossein; Alizadeh-Sani, Mahmood; Pourmand, Mohammad Reza; Azimi, Taher
Abstract: Staphylococcus aureus ( S.aureus ) is a Gram-positive bacterium that causes many infections and diseases. This pathogen can cause many types of infections such as impetigo, toxic shock syndrome toxin (TSST1), pneumonia, endocarditis, and autoimmune diseases like lupus erythematosus and can infect other healthy individuals. In the pathogenic process, colonization is a main risk factor for invasive diseases. Various factors including the cell wall-associated factors and receptors of the epithelial cells facilitate adhesion and colonization of this pathogen. S. aureus has many enzymes, toxins, and strategies to evade from the immune system either by an enzyme that lyses cellular component or by hiding from the immune system via surface antigens like protein A and second immunoglobulin-binding protein (Sbi). The strategies of this bacterium can be divided into five groups: A: Inhibit neutrophil recruitment B: Inhibit phagocytosis C: Inhibit killing by ROS, D: Neutrophil killing, and E: Resistance to antimicrobial peptide. On the other hand, innate immune system via neutrophils, the most important polymorphonuclear leukocytes, fights against bacterial cells by neutrophil extracellular trap (NET). In this review, we try to explain the role of each factor in immune evasion. Highlights: S. aureus is isolated from moist squamous epithelium of the anterior nares in 20% of the individuals. The ability of S. aureus to subvert, evade, or tolerate immune responses contributes to its persistence to create infections. S. aureus increases the outcomes of infections by decreasing or delaying the resolution phase of the inflammatory response. S. aureus has many enzymes, toxins, and uses a couple of strategies to evade from the immune system.